2017
DOI: 10.1002/mus.25388
|View full text |Cite
|
Sign up to set email alerts
|

Fibrosis, low vascularity, and fewer slow fibers after rotator‐cuff injury

Abstract: Adaptive changes in vascular endothelial growth factor and dystrophin were likely associated with reduced vascular supply, fatigue resistance, and fibrosis, accompanied by disuse atrophy from mechanical unloading of supraspinatus after tendon tear. Treatment to promote growth and vascularity in atrophic supraspinatus muscle may help improve functional outcome after surgical repair. Muscle Nerve 55: 715-726, 2017.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
32
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(42 citation statements)
references
References 95 publications
8
32
2
Order By: Relevance
“…Delayed angiogenesis results in impaired muscle regeneration in vivo . Previous studies have shown that vascularity is decreased in the SS compared with the contralateral uninjured side following RC tears . In this study, we demonstrate that transplantation of beige FAPs results in improved SS vascularity compared with PBS and no treatment.…”
Section: Discussionsupporting
confidence: 57%
“…Delayed angiogenesis results in impaired muscle regeneration in vivo . Previous studies have shown that vascularity is decreased in the SS compared with the contralateral uninjured side following RC tears . In this study, we demonstrate that transplantation of beige FAPs results in improved SS vascularity compared with PBS and no treatment.…”
Section: Discussionsupporting
confidence: 57%
“…In addition to the FAP differences outlined in our study and how they might relate to differences in FI across muscles, it is also important to consider other factors that could play a role. Differences in muscle characteristics such as fiber‐type composition, vascularity, and biomechanical function may also impact the type and degree of muscle pathology that develops after different kinds of injury . For example, FAPs have been shown to cluster in perivascular regions .…”
Section: Discussionmentioning
confidence: 99%
“…The expression of miR‐18 was described to negatively correlate with age and thus, repression was correlated with the overexpression of pro‐fibrotic genes . Fibrotic responses are central to the development of chronic tendinopathy, affecting the tendon‐bone junction but also affecting repair processes after tendon microruptures, ultimately leading to biomechanically inferior tendon tissue . Several studies have also reported a pro‐fibrotic role for miR‐192 in TGF‐β‐dependent renal fibrosis which was observed in rodent models of kidney disease …”
Section: Discussionmentioning
confidence: 99%